Influence of school location and gender on generative learning model on secondary school students' academic achievement in chemistry - Obikezie, Maxwell Chukwunazo; Nwuba, Izunna Shedrack; Ibe, Franklin Nnanna (S&Co Publishing, 2023)
This study investigated the influence of school location and gender on the generative learning model's impact on academic achievement in Chemistry among secondary school students in the Awka Education zone, Anambra State. The study employed a quasi-experimental design and used two research questions and two hypotheses as guidance. The sample consisted of 143 senior secondary school one (SS1) Chemistry students in the zone, comprising 73 males and 110 females. From the 49 co-educational secondary schools in the zone, four were selected using a simple random technique. Two schools were assigned to urban locations (47 males and 67 females), while the other two were assigned to rural locations (26 males and 43 females) through simple random sampling by balloting. Fifty Chemistry achievement tests (CAT) were adapted from West African Examination Council (WAEC) objective past question papers. The instruments were validated by experts in the science education department and education foundation. CAT reliability was established using Kudar Richardson 20 (KR-20), which yielded a reliability coefficient of 0.87. To address the research questions, mean and standard deviation were utilized, while the analysis of covariance was employed to test the hypotheses at a significance level of 0.05. The study found that the generative learning model improved student achievement in both urban and rural schools, with a significant difference in mean achievement scores between the two groups. Specifically, the generative learning model proved more beneficial for students in urban schools, particularly for male students. Based on these findings, the study draws conclusions and provides recommendations.